Note on Upper Bounds for TSP Domination Number - Gutin, Gregory; Koller, Angela; Yeo, Anders (Algorithmic Operations Research, 2006)
The domination number, domn(A, n), of a heuristic A for the Asymmetric TSP is the maximum integer d = d(n) such that, for every instance I of the Asymmetric TSP on n cities, A produces a tour T which is not worse than at least d tours in I including T itself. Two upper bounds on the domination number are proved.